Biological Events in Periodontal Ligament and Alveolar Bone Associated with Application of Orthodontic Forces - L. Feller; R. A. G. Khammissa; I. Schechter; G. Thomadakis; J. Fourie; J. Lemmer (The Scientific World Journal)
Orthodontic force-induced stresses cause dynamic alterations within the extracellular matrix and within the cytoskeleton of cells in the periodontal ligament and alveolar bone, mediating bone remodelling, ultimately enabling orthodontic tooth movement. In the periodontal ligament and alveolar bone, the mechanically induced tensile strains upregulate the expression of osteogenic genes resulting in bone formation, while mechanically induced compressive strains mediate predominantly catabolic tissue changes and bone resorption. In this review article we summarize some of the currently known biological events occurring in the periodontal ligament and in the alveolar bone in response to application of orthodontic forces and how these facilitate tooth movement.